Searching for ancient Aegean administrators: computational experiments on identical seal impressions - Finlayson, Sarah; Bogacz, Bartosz; Mara, Hubert; Panagiotopoulos, Diamantis (Journal of archaeological science, 2021)
Seals and sealings were widely used in Neopalatial Crete, primarily in community-wide administrative systems to manage the movement and storage of goods, but also to secure or control channels of intra-site communication using parchment documents. The main principle of this monitoring process was the use of the seal impression as an ‘indexical’ sign, that is, as a means of identifying a seal-user who was acting in an authorising or securing role. Given the fact that seal-users could be acting on their own behalf or, alternatively, as representatives of an institution, there is uncertainty in the literature still over whether the seal impression stood for a single identifiable individual or not. In this paper, we present a new computational methodology for identifying and quantifying similarity within sets of multiple seal impressions made by the same seal. Using a combination of visualisations derived from computational analysis of 3-D scans, experimental work to make seal impressions, and scrutiny of the relevant sealing casts within the Corpus of Minoan and Mycenaean Seals, Heidelberg, we are able to identify groups of sealings impressed in significantly similar ways. We consider it probable that seal impressions with a high degree of similarity were made by the same individual or by two or more people trained to work in a very specific way. This computational methodology is transferable and would prove valuable for other collections of material with identifiable repeated visual elements, such as coins. The implications of our research and the nuance it adds to reconstructions of Neopalatial sealing practices are of broader relevance for sphragistic studies, and provide a point of comparison with the contemporary sealing material of the Ancient Near East.
Gesehen am 22.11.2021